2015
DOI: 10.1136/bmj.h6544
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen versus fosfomycin for uncomplicated urinary tract infection in women: randomised controlled trial

Abstract: STUDY QUESTIONCan treatment of the symptoms of uncomplicated urinary tract infection (UTI) with ibuprofen reduce the rate of antibiotic prescriptions without a significant increase in symptoms, recurrences, or complications? METHODSWomen aged 18-65 with typical symptoms of UTI and without risk factors or complications were recruited in 42 German general practices and randomly assigned to treatment with a single dose of fosfomycin 3 g (n=246; 243 analysed) or ibuprofen 3×400 mg (n=248; 241 analysed) for three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
277
2
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(307 citation statements)
references
References 29 publications
(38 reference statements)
11
277
2
17
Order By: Relevance
“…Es claro que en la presente investigación, aunque se redujo la necesidad total de antibióticos en el grupo de ibuprofeno no se presentó un beneficio sintomático para las pacientes. Además, los casos de pielonefritis fueron más frecuentes en el grupo de ibuprofeno, aunque sin diferencias estadís-ticamente significativas dada su baja ocurrencia (17). Estos resultados no cierran definitivamente la posibilidad de que en las mujeres que presenten síntomas leves o tengan cuadros clínicos dudosos, se considere de común acuerdo la posibilidad de retrasar el inicio del antibiótico e incluso de no prescribirlo en algunos casos.…”
Section: Período De Seguimiento: 28 Díasunclassified
See 1 more Smart Citation
“…Es claro que en la presente investigación, aunque se redujo la necesidad total de antibióticos en el grupo de ibuprofeno no se presentó un beneficio sintomático para las pacientes. Además, los casos de pielonefritis fueron más frecuentes en el grupo de ibuprofeno, aunque sin diferencias estadís-ticamente significativas dada su baja ocurrencia (17). Estos resultados no cierran definitivamente la posibilidad de que en las mujeres que presenten síntomas leves o tengan cuadros clínicos dudosos, se considere de común acuerdo la posibilidad de retrasar el inicio del antibiótico e incluso de no prescribirlo en algunos casos.…”
Section: Período De Seguimiento: 28 Díasunclassified
“…De los 4 estudios de bioimpedancia (n = 1039), uno evaluó el Análisis de Impedancia Bioeléctrica (AIB) convencional y 3 estudiaron el Análisis Vectorial de Impedancia Bioeléctrica (AVIB). Cuando se reportaba un AIB segmentario de 54 ohmios o menos, el LR era de 10,6 (IC95 % = 5, [8][9][10][11][12][13][14][15][16][17][18][19]2). Sin embargo, un solo estudio analizó este punto de corte (n = 292) y se consideró que el riesgo de sesgo era muy alto por las exclusiones de los pacientes con base en comorbilidades que causaran ascitis y edema periférico.…”
Section: Diagnóstico De Falla Cardíaca Aguda En El Departamento De Emunclassified
“…Ibuprofen vs fosfomycin Gágyor et al 6 conducted a double-blind, randomized multicenter trial in 42 general practices in Germany to assess whether treating the symptoms of uncomplicated urinary tract infection with ibuprofen would reduce antibiotic use without worsening outcomes.…”
Section: -11mentioning
confidence: 99%
“…1 Several small studies have suggested that many of these infections are self-limited, resolving within 3 to 14 days without antibiotics ( Table 1). [2][3][4][5][6] A potential disadvantage of withholding treatment is slower bacterial clearance and resolution of symptoms, but reducing the number of antibiotic prescriptions may help slow antibiotic resistance. 7,8 Surveys and quali- On days 0-4, patients in the ibuprofen group had more symptoms than those in the fosfomycin group a Participants in these studies were not pregnant.…”
Section: Urinary Tract Infections Are Often Self-limitedmentioning
confidence: 99%
“…diclophenac) used for rheumatic diseases have an unexpected antimicrobial activity and are able to cure urinary tract infections [30][31][32].…”
Section: Consequences Of the Two-sided Effect Of Psychotherapeutic Drmentioning
confidence: 99%